Implikasi Prinsip Exhaustion Terhadap Sengketa Impor Paralel Merek Dagang (Trademark) - Dhiaulhaque, Nada; Jayakusuma, Zulfikar; Putri, Adi Tiara (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Marks is a name and/or symbol that is used by a company that has been developed by the companyto symbolized their reputation and to placed their products in the market. Lately, in the revolution oftrading, one of the problem that are oftenly happens are parallel imports. Parallel imports is a confusingoccurance, in one hand it is a distribution of original products the other hand its distribution is notpermitable by the intellectual property rights holder and/or licensor. Parallel imports occurs ininternational trade and it is hard to solve it, every state has their own “exhaustion of rights”.This research used a normative research methode, it’s starting points begins from the lawperspective field (textual), with identifying to its formulable norm. This research is descriptive research todescribe the actual event when the research was held, through collecting data and interpretated one anotherso it will give a proper formula and analysis to the existing problem. The data source is secondary soucethat consist of primary material, secondary material, and tertier material.From this research we can conclude, first, exhaustion of rights that occur within the article 6 ofTRIPs always become the loophole for the parallel imports defendants, with the exhaustion of rights withinthis upnormal situation, it could give a long-term effects to the product that are effected by the parallelimportation. Starting from the reduced investment, hampered innovation, goodwill contaminated, also therapid development of channels of parallel import of sheltering the perpetrators behind article 6 TRIPs.Secondly, exhaustion of rights that is happening within every state would be different in their application.This depends on what kind of “exhaustion” they’re using. The exhaustion of rights also affect how theintellectual property rights holder exclusive right and/or the licensor in controlling of their products.Keywords : Parallel Imports, Trademark, Exhaustion of Rights, Exclusive Right, Intellectual Property Right.